Smartphone Use and Multitasking Behaviour in a Teacher Education Program (TEP) - Hikmat, Ade; Mulyono, Herri (International Journal of Interactive Mobile Technologies (iJIM), 2018)
This paper reports on a small scale investigation into preservice teachers’ multitasking behaviours during a course in a teacher education program (TED). Specifically, it addresses three research questions, 1) how frequent do preservice teachers do multitasks with smartphone, 2) what are the types of preservice teachers’ multitasking behaviour, and 3) to what extent does multitasking behaviour affect preservice teachers’ learning. To this end, we did a classroom observation where smartphone was used to facilitate learning. During the observation, we wrote notes concerning preservice teachers’ multitasking behaviour with their smartphone. In addition, a total of 35 preservice teachers was surveyed. Findings of this study show that 97.14% of preservice teachers do multitasking in class; although the frequency and types of multitasking with smartphone vary. The findings also highlight fifteen types of multitasking behaviour with two most common activities: texting and searching. The analysis of preservice teachers’ responses on the survey as well as the observation data suggest that multitasking behaviour contributes both positively and negatively to preservice teachers’ learning. In reference to the findings, implications of the study to TEP are offered.